The EFFECT OF HEALTH EDUCATIONAL PROGRAM ON HYPERTENSION TOWARD KNOWLEDGE AMONG POPULATION - Wahyuningsih, Tri; Selviana, Ressa (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Hypertension is a major health problem in the world. According to data from the World Health Organization (WHO) in 2011, 26,4% of the world’s population suffers from hypertension and is likely to increase to 29,2% by 2025. Hypertension is a condition of increased blood pressure, both systolic and diastolic, which is equal to or more than 140/90 mmHg. Hypertension can interfere with the function of other organs, especially vital organs such as the heart and kidneys and brain. Therefore, the community needs to understand hypertension, its prevention and how to overcome it. This counseling aims to increase public knowledge about the management of hypertension so that the community are compliant in treatment and is able to prevent hypertension. The methods used are presentation, discussion and evaluation through pre and post test. The results of the activity showed an increase in participants understanding of hypertension. This counseling succeeded in providing insight to participants about hypertension, hypertension prevention and hypertension management, however this acitivity must continue to be carried out continuously so that public understanding is maintained